Preliminary phytochemical evaluation and analysis of inorganic elements on Physalis minima l. - C. KARPAGA SUNDARI; S. KULOTHUNGAN (International Journal of Pharma and Bio Sciences, 2018)
Physalis minima L. belongs to the family Solanaceae, is a common weed throughout the plains of India. The aim of the present study is to evaluate the phytochemical analysis of and inorganic elements of leaves extract using different solvents like aqueous, methanol, chloroform and diethyl ether. Among the four extracts, methanolic leaves extract indicates the maximum number of phytoconstituents such as alkaloids, reducing sugar, flavonoids, steroids, tannins and carbohydrates. In the inorganic elements of methanolic leaf extract were investigated, the plant P.minima L. leaves have considerable amount of mineral elements. The results showed that the extract of Physalis minima L. leaves have a significant phytochemical compound and support its traditional uses in herbal medicine.